2023
DOI: 10.1099/jmm.0.001741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the follicular fluid microbiota based on culturomics and sequencing analysis

Abstract: Introduction. The human oocyte microenvironment is follicular fluid, which is important for follicle growth, ovulation and maturation of the oocyte. The micro-organisms present in follicular fluid could be a predictor of in vitro fertilization outcomes. Hypothesis/Gap Statement. Women with follicular fluid colonized with micro-organisms can be asymptomatic, but the presence of some genera in the follicular fluid correlates with in vitro fertilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…58 A recent study identified via culturomics Streptococcus, Finegoldia, and Peptoniphilus in follicular fluid from patients undergoing IVF treatment. 62 The same study also performed molecular methods (i.e., 16S rRNA gene sequencing) to analyze the microbiome in follicular fluid, revealing a composition of Pseudomonas, Lactobacillus, Comamonas, Streptococcus, and Acinetobacter. 62 Although it has been suggested that microorganisms in the follicular fluid and ovarian tissue may originate from contamination from the female reproductive system or from surgical handling, increasing research indicates that these anatomical sites have their own microbial compositions.…”
Section: Microbial Composition Of the Ovariesmentioning
confidence: 99%
See 1 more Smart Citation
“…58 A recent study identified via culturomics Streptococcus, Finegoldia, and Peptoniphilus in follicular fluid from patients undergoing IVF treatment. 62 The same study also performed molecular methods (i.e., 16S rRNA gene sequencing) to analyze the microbiome in follicular fluid, revealing a composition of Pseudomonas, Lactobacillus, Comamonas, Streptococcus, and Acinetobacter. 62 Although it has been suggested that microorganisms in the follicular fluid and ovarian tissue may originate from contamination from the female reproductive system or from surgical handling, increasing research indicates that these anatomical sites have their own microbial compositions.…”
Section: Microbial Composition Of the Ovariesmentioning
confidence: 99%
“…62 The same study also performed molecular methods (i.e., 16S rRNA gene sequencing) to analyze the microbiome in follicular fluid, revealing a composition of Pseudomonas, Lactobacillus, Comamonas, Streptococcus, and Acinetobacter. 62 Although it has been suggested that microorganisms in the follicular fluid and ovarian tissue may originate from contamination from the female reproductive system or from surgical handling, increasing research indicates that these anatomical sites have their own microbial compositions. However, more research and a more rigorous and homogeneous methodology across studies are needed to establish their microbial composition.…”
Section: Microbial Composition Of the Ovariesmentioning
confidence: 99%